2018
DOI: 10.1016/j.taap.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicin reduces genotoxicity, colonic cell proliferation and preneoplastic lesions induced by 1,2-dimethylhydrazine in rats

Abstract: Capsaicin (8-Methyl-N-vanillyl-(trans)-6-nonenamide) is the major pungent ingredient found in chili peppers consumed worldwide. Most reports on capsaicin potential carcinogenicity have yielded inconsistent findings. Some studies have shown that capsaicin exerts anti-proliferative and pro-apoptotic effects on different cancer cell lines, while others have reported an association between capsaicin at high doses with mutagenicity and carcinogenicity. Thus, this study aimed at assessing the effects of capsaicin ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 70 publications
(71 reference statements)
1
13
0
Order By: Relevance
“…Pre-clinical studies have demonstrated that capsaicin may be a chemopreventive agent in CRC through anti-proliferative, anti-genotoxic, induced expression of apoptotic genes, and up-regulation of genes involved in cell differentiation [177]. Since previous reports indicated that capsaicin might promote metastasis, acting as co-carcinogen in cancer skin [196] and promoting breast cells metastasis [197].…”
Section: In Vivo Studies In Crc Animal Modelsmentioning
confidence: 99%
“…Pre-clinical studies have demonstrated that capsaicin may be a chemopreventive agent in CRC through anti-proliferative, anti-genotoxic, induced expression of apoptotic genes, and up-regulation of genes involved in cell differentiation [177]. Since previous reports indicated that capsaicin might promote metastasis, acting as co-carcinogen in cancer skin [196] and promoting breast cells metastasis [197].…”
Section: In Vivo Studies In Crc Animal Modelsmentioning
confidence: 99%
“…ACF are well known estimators for colon carcinogenesis which are used as end point marker in cancer chemoprevention interventions and indicators for carcinogenesis. They steadily appear in the normally-appearing colorectal mucosa of colon cancer patients (Ghosh et al, 2018) or after DMH administration in rodents (Caetano, 2018). On the other hand, the inhibitory effects of the ASCex here are accompanied with a significant inhibition in the PCNA-LI (%) in colonic mucosa and in tumors.…”
Section: Discussionmentioning
confidence: 86%
“…Con icting reports exists on antitumoral or carcinogenic effects of capsaicin (Friedman et al, 2019). Some studies have shown that capsaicin at 50mg/kg reduced CRC risk in DMH-induced rats models by inhibiting the cytotoxicity, genotoxicity, proliferation, and apoptosis of cancer cell/tissue (Caetano et al, 2018). They also showed that high dose capsaincin decrease the proportion of tubular .…”
Section: Discussionmentioning
confidence: 99%